YAP promotes myogenic differentiation via the MEK5‐ERK5 pathway. Issue 7 (29th March 2017) - Chen, Ting‐Huan; Chen, Chen‐Yu; Wen, Hui‐Chin; Chang, Chia‐Chu; Wang, Horng‐Dar; Chuu, Chih‐Pin; Chang, Chung‐Ho
ABSTRACT: Yes‐associated protein (YAP) is a transcriptional coactivator in the Hippo pathway that regulates cell proliferation, differentiation, and apoptosis. The MEK5/ERK5 MAPK cascade is essential for the early step of myogenesis. In this study, we generated C2C12 stable cell lines that expressed YAP (C2C12‐YAP cells) and found that ERK5 and MEK5 were activated in C2C12‐YAP cells compared with control C2C12 (C2C12‐vector) cells. C2C12YAP stable cells also differentiated into myotubes better than C2C12‐vector cells, and expressed elevated levels of myogenin, a transcription factor that regulates myogenesis, as well as elevated levels of myosin heavy chain, a skeletal muscle marker. Western blot analysis revealed that Src and c‐Abl (Abelson murine leukemia viral oncogene homolog 1) activation were enhanced in C2C12‐YAP cells. Conversely, treatment of inhibitors of c‐Abl, Src, or MEK5 inhibited activation of MEK5 and ERK5 and myogenesis of C2C12 myoblasts. Specific interactions between YAP and proteins in the ERK5 pathway, such as MEK kinase 3 (MEKK3) and ERK5, were illustrated by coimmunoprecipitation experiments. MEKK3 contains the PPGY motif (aa 178–181), which may interact with YAP. Site‐directed mutagenesis experiments revealed that expression of MEKK3 Y181F mutant inhibited MEK5/ERK5 activation and myogenic differentiation. These results suggest that YAP promotes muscle differentiation by activating the Abl/Src/MEKK3/MEK5/ERK5 kinase cascade.—Chen, T.‐H., Chen, C.‐Y., Wen, H.‐C., Chang, C.‐C., Wang, H.‐D., Chuu, C.‐P., Chang, C.‐H. YAP promotes myogenic differentiation via the MEK5‐ERK5 pathway. FASEB J. 31, 2963–2972 (2017). www.fasebj.org